Determinants in Fraud Detecting (Empirical Study at Audit Agency of the Republic of Indonesia and the Financial and Development Supervisory Agency Lampung) - Sigit Arie Wibowo; Putri Puspa Dewi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to test factors that influence the auditor's ability to detect fraud (empirical study on BPK representative of Lampung and BPKP representative of Lampung). This research is a quantitative study using primary data and obtained through a questionnaire. The subjects in this study were auditors working at the BPK representative of Lampung and BPKP representative of Lampung. In this study the sample amounted to 100 respondents with a purposive sampling method, that is to use all populations that have criteria for auditors who work more than one year.The results of the study state that red flags and independence have a positive effect on the auditor's ability to detect fraud. Meanwhile competence, professional skepticism, and fraud schemes do not affect the auditor's ability to detect fraud.